Operation mode and scheduling plan optimization approach for multiple balancing zones in a distribution system - Huang, Kai; Yi, Zhongkai; Xu, Ying; Zhou, Zhaozheng; Han, Liu (Frontiers in Energy Research, 2024)
The modern power system is advancing rapidly, distributed energy, energy storage devices, adjustable loads, and other flexible resources are consolidated through microgrids, virtual power plants, and integrated source-network-load-storage systems. This consolidation under various balancing zone models facilitates synergistic operations, becoming a critical approach to enhance distributed power consumption and ensure the reliability of electricity supply. In light of this, facing the challenges of inadequate economic efficiency, reduced accommodation of renewable energy, and poorer operational reliability in distribution networks, this paper proposes a category selection and flexibility resource scheduling method that considers the differences in multiple balancing zone models and modes. Firstly, the approach establishes a multi-dimensional characteristic evaluation index and multiple balancing zone operation models. Subsequently, the characteristic evaluation indicators are utilized to assess the unique properties of the balancing zone system and eliminate unreasonable operating modes. Finally, through analyzing the effectiveness and differences of various balancing zone operation modes, the optimal operation mode is selected, and a scheduling plan is formulated. The conclusion is that the scheduling plan optimization method considering the operation mode can realize the reasonable choice of operation mode and achieve the purpose of benefit optimization.